2019
DOI: 10.3390/genes10110903
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping Array Design for Multi-Ethnic Studies of Multiple Sclerosis

Abstract: While approximately 200 autosomal genetic associations outside of the major histocompatibility complex (MHC) have been identified for multiple sclerosis (MS) risk in European populations, causal variants identified at the majority of these associated loci have been much more elusive. We propose that knowledge gained from replication efforts in Hispanic and African American populations can be utilized to more efficiently fine-map these risk loci. To this end, we have customized a genotyping array by adding ~20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The current study focused on imputed genomic array data within the MHC containing rich information in genetic ancestry, population genomics, and MS susceptibility. Future research can integrate additional -omics data; including but not limited to transcriptomics, epigenomics, proteomics, and pharmacogenomics to further decipher the relationship between genetic ancestry and MS susceptibility within the MHC and within other known MS loci [ 45 ]; facilitating a comprehensive understanding of precision population health.…”
Section: Discussionmentioning
confidence: 99%
“…The current study focused on imputed genomic array data within the MHC containing rich information in genetic ancestry, population genomics, and MS susceptibility. Future research can integrate additional -omics data; including but not limited to transcriptomics, epigenomics, proteomics, and pharmacogenomics to further decipher the relationship between genetic ancestry and MS susceptibility within the MHC and within other known MS loci [ 45 ]; facilitating a comprehensive understanding of precision population health.…”
Section: Discussionmentioning
confidence: 99%
“…The first genetic analyses performed in multiple sclerosis were anonymous genome analyses based on the linkage analysis of the microsatellite markers in multiplexed families. Although they allow the identification of regions of interest outside the MHC, their participation in replication studies cannot be confirmed [41,54,55]. These studies have focused on designing genome-wide arrays aimed at identifying causal variants.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…Replication studies that focus on the lead SNP at a locus identified in a European population are, by design, primarily concerned with replication of known signals rather than discovery of heterogeneity in associated loci or alleles across populations. These efforts will be advanced by the development of new genotyping arrays designed specifically for cross-ancestry association testing and fine mapping 76 , and by decreasing sequencing costs, which could make sequencing feasible on a consortium scale.…”
Section: [H1] Beyond the Mhcmentioning
confidence: 99%
“…Identifying sufficiently large numbers of patients with disease can be difficult and is complicated by differential access to healthcare facilities, phenotypic heterogeneity and a low incidence in some populations. We anticipate that the increasing number of international efforts to do this work will eventually lead to GWAS in populations of non-European ancestry with comparable sample sizes and statistical power to studies in populations of Europeanancestry 76 .…”
Section: [H1] Challengesmentioning
confidence: 99%